RANCANG BANGUN SISTEM INFORMASI KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX - Cecep Kurnia Sastradipraja; Rindi Atika Barokah (P3M- Politeknik Negeri Kupang, 2020)
This study aims to measure the impact of perceptions of health service quality on patient satisfaction at the Baros Sukabumi Community Health Center. Based on these objectives, research is carried out through the development of a web-based information system using a 'SERVQUAL' based instrument which uses five dimensions of service quality, namely: physical evidence, empathy, management, responsiveness, assurance, and empathy. To measure customer satisfaction based on the attributes to be measured is by using the customer satisfaction index method. The survey was conducted to collect data with a total of 105 respondents. The evaluation system is carried out with descriptive and inferential statistical techniques which are used to test the hypothesis, and the method of testing methods uses the blackbox. Based on the research results, it shows that the system built can produce the expected information, namely the effect of service quality on patient satisfaction and chicken at Baros Sukabumi Health Center.